Characteristics of current smokers versus former smokers with COPD and their associations with smoking cessation within 4.5 years: results from COSYCONET - Alter, Peter; Stoleriu, Cosmina; Kahnert, Kathrin; Henke, Markus Oliver; Bals, Robert; Trudzinski, Franziska; Watz, Henrik; Speicher, Tim; Söhler, Sandra; Welte, Tobias; Rabe, Klaus F.; Wouters, Emiel Frans Maria; et al. (The International journal of chronic obstructive pulmonary disease, 2023)
Evaluating whether patients with COPD who smoked differed from patients with COPD who had ceased smoking prior to inclusion or during the follow-up study time
Gesehen am 27.06.2024